PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MENGINAP (STUDI PADA RESEPSIONIS HOTEL ON THE ROCK KUPANG) - Afifah A.B. Ikram; Antonio E.L. Nyoko; Ronald P C Fanggidae (Universitas Nusa Cendana, 2019)
The purpose of this study was to determine the effect Services Quality by recepsionits to customer satisfaction. The population in this study were guests who stayed at the On The Rock Hotel. The sample amount was 50 conducted randomly to the guests. Data processing and analysis is carried out using the SPPS program. The results of this study indicate that the sub variables of Service Quality (Physical Evidence, Emphaty, Reliability, Responsiveness, and Assurance) have a simultaneously significant effect on Customer Satisfaction who stay in the hotel. Keywords: Quality Services, Customer Satisfaction.